Trust and the Influence of Social Media Marketing, Influencers, Flow State on Online Impulsive Buying - Dwi Novitasari; Prafidhya Dwi Yulianto; Annisa Fitrianingrum; Desy Silvia Rachmawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Abstract. Internet user access in Indonesia is increasing annually, with the internet primarily used for accessing various application platforms, especially social media. Social media users now prefer platforms with complete features for information, chatting, and shopping. This trend has led to issues regarding shopping behavior on social media, which offers attractive deals through celebrity endorsements, easy access to finance, and greater convenience than direct shopping. This study aims to analyze Social Media Marketing (SMM), influencers, flow state, and trust mediation in online impulsive buying behavior. This research also includes a perspective from accounting or finance, namely mental accounting on online impulsive buying behavior which, based on previous literature, has not been widely used so far. The research approach used is quantitative with a cross-sectional design, with a sample of shoppers on the TikTok application. Data analysis uses the Structural Equation Model (SEM) technique. The findings show that flow states play a direct role in online impulsive buying where SMM and influencers do not. The next finding is that trust plays a full mediating role in the influence of SMM, influencers, and flow state on online impulsive buying.